Unusually large Mongolian blue spots in GM1 gangliosidosis: Is there an association? - Senanayake, M. P.; Dissanayake, P. V.; Rupasinghe, S.; Seneviratne, J. K. K. (Sri Lanka College of Paediatricians, 2010)
GM1 gangliosidosis is a rare storage disorder in which accumulation of sphingolipids occurs in brain and viscera due to a deficiency of a lysosomal enzyme. Multiple and unusually large Mongolian blue spots have been postulated to be an associated feature of lysosomal storage disorders 1,2 . Our patient, whose clinical course and physical signs were in keeping with GM1 gangliosidosis, had extensive Mongolian blue spots and this adds to the evidence supporting such an association. Case Report A seven month old girl, born by normal delivery to consanguineous parents, presented with developmental regression. Coarse facial features including low set ears, broad nasal bridge, a long philtrum and frontal bossing were present but there were no corneal opacities or macular cherry red spots. She had hepatosplenomegaly, hypotonia with brisk tendon reflexes, poor response to auditory stimuli and global developmental delay. A blue-black, maculopapular rash with clear margins resembling angiokeratoma had appeared symmetrically in the "bathing trunk area" at age four months (Figures 1, 2 & 3). Face, trunk and upper limbs were spared. In addition, large hyperpigmented, well demarcated macules resembling Mongolian blue spots were scatterd all over the body since birth. Psychomotor regression coincided with the appearance of angiokeratoma. Urine was weakly positive for dermatan sulphate. Radiography showed anterior beaking of the lower part of vertebrae and oar shaped ribs. Beta galactosidase assay was not available but clinical differentiation from mucopolysaccharidosis (type 1) was possible, based on the absence of corneal opacities and the presence of angiokeratoma.
Keywords: Mongolian blue spots; GM1 gangliosidosis